"Brr! It's cold in here" measures of household energy insecurity for the United States. (February 2021) - Harker Steele, Amanda J.; Bergstrom, John C.
Highlights: Energy insecurity is a multi-dimensional construct. Energy-service related hardships lead to felt levels of energy insecurity. Dichotomous Rasch model generates a valid index measure of energy insecurity. In 2015, between 9 and 22% of U.S. households identified as energy insecure. Abstract: Relatively little research thus far has been done to identify and measure the extent of household energy insecurity in the United States. One factor contributing to the lack of research is the absence of a single, consistent, and universally accepted energy insecurity index measure. This paper addresses this gap in the literature by estimating and comparing alternative empirical procedures available to generate an energy insecurity index using data from the 2015 Residential Energy Consumption Survey. Results suggest that in 2015 between 9 and 22% of U.S. households surveyed identified as energy insecure. The extent of energy insecurity experienced, however, varied based on which empirical procedure was used to construct the index. Examination of the content, construct, and convergent validity of the results suggests the dichotomous Rasch model provides a conceptually, empirically strong, and valid index for measuring the extent of household energy insecurity.